Complications during the Management of Dislocated Tracheostomy Cannula - Kristian Krogh; Anette Marianne Fedder (Case Reports in Critical Care)
We describe an acute complication to a tracheostomy cannula in the form of a dislocated cannula after a surgical tracheostomy in a 65-year-old male patient. The case illustrates the development of progressing subcutaneous emphysema resulting in a cannot intubate, cannot oxygenate (CICO) situation and the airway management of the patient with respiratory distress. Early recognition and situational awareness are essential in the management of patients with acute airway complications. Consequently, deliberate practice and continuing professional development should be encouraged so that we can best manage acute situations when they occur.